IMPLEMENTASI MODEL PEMBELAJARAN BERBASIS MASALAH DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IV DI SDN 14/1 SUNGAI BAUNG - Mulyanti, Sri; Nuraini; Dies Yunizha , Thera; Destrinelli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The results of this research include initial data that researchers obtained from the daily tests of class IV students at SDN 14/1 Sungai Baung for the 2024/2025 academic year, then improvements were made with the aim of improving critical thinking skills in the classroom. IV Indonesian language learning uses the Problem Based Learning (PBL) model. Classroom Action Research (PTK) is carried out in two cycles consisting of four stages, namely planning, implementation, observation and reflection. In Cycle 1 the material taught is Main and Supporting Ideas. Of the 21 students, only 3 students (14.29%) obtained a score above the KKM (70), with a class average score of 56.43. In Cycle 2 the material taught is Reading and Seeing. All 21 students scored above the KKM (70), with an average class score of 80.48, which indicates 100% classical completion. This increase occurs because students are more active in learning, pay attention to teacher explanations, and dare to ask and answer questions. The research results show that the PBL model is effective in improving student learning outcomes. Keywords: critical thinking ability, elementary education, problem based learning model